Pan-Canadian Arctic Cycling of Marine Dissolved Organic Carbon and Nitrogen - O'Reilly, Lauren (Université d'Ottawa | University of Ottawa, 2024)
Marine dissolved organic matter (DOM; <0.1µm) is one of Earth’s largest reservoirs (662 GtC; 32-70 GtN) of reactive carbon (as dissolved organic carbon; DOC) and nitrogen (as dissolved organic nitrogen; DON). It is produced autochthonously in the ocean through primary production via fixation of atmospheric CO2 or can be delivered allochthonously, primarily from riverine or atmospheric input (Hansell et al., 2009). The lifetimes of DOM in the ocean span from minutes to millenia, with most DOM being rapidly consumed and remineralized in the surface ocean by heterotrophic microbes. However, the portion that is not consumed comprises small dissolved and colloidal molecules that resist biological degradation and accumulate in the ocean, playing a critical role in global atmospheric carbon sequestration and climate modulation (Benner & Amon, 2015). DOM biogeochemistry of the Canadian Arctic is largely unconstrained despite the region being exacerbated by the impacts of global climate change and currently warming four times faster than the rest of the planet (Rantanen et al., 2022). The Canadian Arctic Archipelago (CAA) and Baffin Bay connect Arctic, Pacific, and Atlantic-origin waters to the North Atlantic and are thus key regions of DOM production, delivery and transformation that will be translated into North Atlantic Deep Water (NADW) and potentially stored for centuries to millenia via global thermohaline circulation. Baseline DOC and DON concentrations, with respective elemental stoichiometry (C:N), are needed for the Canadian Arctic as they can be used as basic indicators of carbon and nitrogen sources, sinks and chemical transformation which are necessary in order to understand their contribution to global carbon and nitrogen cycles. Only surface values have been reported for DOC and DON in the CAA and Baffin Bay to date, with no published data regarding carbon and nitrogen stoichiometry. Here we report the first depth profiles of DOC and DON concentrations with stoichiometric ratios (DOM C:N) in the CAA and Baffin Bay. We evaluate these data considering DOM sources, bioavailability and removal mechanisms in the Canadian Arctic. We find that DOC and DON cycling are decoupled in the Canadian Arctic. DOC is significantly higher in CAA surface and Pacific Winter Water (~200m) than in Baffin Bay. We quantify contributions of terrestrial and marine DOM using a δ18O proxy and find a loss of both terrestrial and marine DOM from the CAA to Baffin Bay, suggesting removal of DOM with lateral transport into Baffin Bay and along the Baffin Island Current (BIC) before entering the Labrador Sea. We identify three regions of very high DON and low DOM C:N: the North Water Polynya, Davis Strait, and an upwelling region in the Amundsen Gulf, suggesting labile DOM production and export and/or the accumulation of recalcitrant DON. We find that the CAA and Baffin Bay differ with respect to biogeochemical cycling. Our results support previous work suggesting Baffin Bay as a source of labile DOC fueled by high primary productivity, however our study also suggests it is a sink for primarily marine, but also high C:N terrestrial DOM from the CAA that is removed within the BIC. In contrast, DOM in the CAA may be more strongly controlled by marine microbial loop processes and the microbial transformation of terrestrial DOM into more recalcitrant, high C:N compounds. Finally, we observe that the Kitikmeot Sea has unique DOM biogeochemistry, with very high DOC at depth (~300m) and high DOM C:N, possibly explained by large contained freshwater inputs and enhanced heterotrophy. We identify the CAA and Baffin Bay as previously unrecognized sinks of both terrestrial and marine DOM and estimate removal rates of DOM along key advective pathways in the Canadian Arctic. These results provide a critical baseline understanding of DOM biogeochemical cycling in the Pan-Canadian Arctic which aid in quantifying the impact of climate change on Arctic DOM reservoirs.
Keywords: dissolved organic carbon; dissolved organic nitrogen; reactivity; terrestrial; marine; Arctic